PENDAMPINGAN MENDIDIK ANAK DI ERA DIGITAL BAGI GURU DAN ORANG TUA MURID (WIKUACITYA: Jurnal Pengabdian Kepada Masyarakat, 2024)
Educating children in the digital era requires sufficient knowledge and understanding from educators and all parties involved in it. Parents also play a very important role in the success of children's education because the same perception in education is very important in supporting the success of the educational process. In order to equalize perceptions between teachers and parents regarding how to educate children in the digital era, this community service program aims to provide knowledge about how to educate and accompany children in the digital era for teachers and student guardians at the TK Muslimat NU Dippnegoro 51 Batuanten, Cilongok District , Banyumas Regency. The method used in this service is counseling and mentoring delivered directly by the Assistance Team. The results of the service program show that participants enthusiastically welcomed the material presented and participants were able to apply protection to digital applications so that children could avoid the negative impacts of digital content.